Tropical forests & global atmospheric change - Malhi, Y. (Yadvinder); Phillips, Oliver (EBSCO eBook collection., 2005)
This text explores the vigorous contemporary debate as to how rapidly tropical forests may be affected by atmospheric change, and what this may mean for their future.